2003
DOI: 10.1159/000074268
|View full text |Cite
|
Sign up to set email alerts
|

Can Three-Dimensional Ultrasound Be Used for the Assessment of the Fetal Lung Volume in Cases of Congenital Diaphragmatic Hernia?

Abstract: We report on 2 fetuses with congenital diaphragmatic hernia (CDH) in whom the fetal lung volumes were estimated by three-dimensional ultrasound and the results compared with the postmortem lung volume measurements. Both examiners (sonographer and pathologist) were blinded to each other’s results. The 1st case was a right CDH diagnosed at 20 weeks of gestation. The 2nd case was a left CDH diagnosed at 22 weeks of gestation. Both pregnancies were terminated upon request of the parents. Three-dimensional ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 14 publications
(19 reference statements)
3
51
0
2
Order By: Relevance
“…Ipsilateral fetal lung volumes were measured by the same technique previously described in the literature [19][20][21][22][23] , using a Voluson 730 ultrasound machine (Kretztechnik, General-Electric, Zipf, Austria) with a 4-to 8-MHz transducer for three-dimensional volume scanning. A transverse section of the fetal thorax at the level of the four chamber view, with the fetal heart proximal to the transducer, was identified by 2DUS and the volume box was adjusted in order to scan the entire fetal thorax.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipsilateral fetal lung volumes were measured by the same technique previously described in the literature [19][20][21][22][23] , using a Voluson 730 ultrasound machine (Kretztechnik, General-Electric, Zipf, Austria) with a 4-to 8-MHz transducer for three-dimensional volume scanning. A transverse section of the fetal thorax at the level of the four chamber view, with the fetal heart proximal to the transducer, was identified by 2DUS and the volume box was adjusted in order to scan the entire fetal thorax.…”
Section: Methodsmentioning
confidence: 99%
“…Total and contralateral fetal lung volumes can be measured precisely on 3DUS [23,24] correlating significantly with neonatal deaths [21,24] . Total fetal lung can be calculated using the rotational technique (VOCAL TM ) by summing the right and left lung volumes [19][20][21][22][23] . Initial results showed that an observed/expected total fetal lung volume ratio (o/e-TotFLVR) lower than 0.35 was significantly associated with neonatal deaths [21] , confirming the results of previous studies using MRI [15][16][17][18] .…”
mentioning
confidence: 99%
“…1,7 Nevertheless, in spite of the great advances in prenatal and postnatal diagnosis and management, the mortality rate in neonates with isolated CDH is still high. 8 Recent research has focused on prenatal predictors of neonatal outcome in isolated CDH cases, such as lung/head ratio 9,10 and fetal lung volume, [11][12][13][14][15][16] to differentiate cases with a worse prognosis, in which fetal therapy or termination of pregnancy may be indicated, from those with better prognosis, requiring only specialized postnatal care. [17][18][19] In spite of the worldwide, published experience, there are no data about perinatal results in cases of prenatally diagnosed CDH in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonographic delineation of abnormally small fetal lungs is difficult but feasible and, more recently, threedimensional ultrasound seems promising [4] . Today, definition of unilateral pulmonary hypoplasia is deduced from biometric data of the fetal head and contralateral larger lung defined as the fetal lung-to-head ratio [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic features of prenatal CDH are well-described and evaluated in order to determine prognosis of the fetus [4] . With the recently developed prenatal tracheal occlusion (TO) intervention, criteria for TO have been discussed and only fetuses with a predicted bad neonatal outcome are considered for this intervention [5] .…”
Section: Introductionmentioning
confidence: 99%